1994
DOI: 10.2307/3869680
|View full text |Cite
|
Sign up to set email alerts
|

Fibril Assembly and Carotenoid Overaccumulation in Chromoplasts: A Model for Supramolecular Lipoprotein Structures

Abstract: Chromoplast development in ripening bell pepper fruits is characterized by a massive synthesis of carotenoid pigments, resulting in their distinctive red color. We have shown that 95% of these pigments accumulate in chromoplasts in specific lipoprotein fibrils. In addition to carotenoids, purified fibrils contain galactolipids, phospholipids, and a single, 32-kD protein, designated fibrillin, which has antigenically related counterparts in other species. Fibrils were reconstituted in vitro when purified fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
209
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(224 citation statements)
references
References 31 publications
12
209
0
3
Order By: Relevance
“…In chromoplast PGs, we identified homologs of FIB1a, 1b, 2, and 4. Fibrillins have one or more hydrophobic regions, which have been proposed to play a role in stabilizing the globules and preventing coalescence (Deruere et al, 1994). Importantly, Camara, Kuntz, and colleagues (Deruere et al, Identification of the protein by peptide mass fingerprinting from 1-D PAGE is indicated with the number of the gel band (from the gel in Fig.…”
Section: Fibrillinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In chromoplast PGs, we identified homologs of FIB1a, 1b, 2, and 4. Fibrillins have one or more hydrophobic regions, which have been proposed to play a role in stabilizing the globules and preventing coalescence (Deruere et al, 1994). Importantly, Camara, Kuntz, and colleagues (Deruere et al, Identification of the protein by peptide mass fingerprinting from 1-D PAGE is indicated with the number of the gel band (from the gel in Fig.…”
Section: Fibrillinsmentioning
confidence: 99%
“…PGs were also proposed to play a role in the removal of protein catabolites as part of thylakoid turnover (Ghosh et al, 1994;Smith et al, 2000). In chromoplasts, PGs are the main storage and remodeling site for carotenoids (Deruere et al, 1994). So far, it is not known whether PG proteomes include any enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are 11 or more fibrillin proteins in land plants associated with both plastoglobules and thylakoid membranes. They have one or more hydrophobic regions and are proposed to stud the surface of the plastoglobule to prevent them from coalescing (Deruere et al, 1994). Fibrillin expression increased following the high-light exposure, potentially corresponding to the observed increase in plastoglobule number during stress conditions.…”
Section: What Was Shownmentioning
confidence: 99%
“…Etioplasts have large numbers of plastoglobules, and increase in plastoglobule size and numbers is also observed during of senescence (for review, see Hopkins et al, 2007). In chloroplasts, plastoglobules contain quinones, a-tocopherol, and lipids, and those in chromoplasts accumulate high levels of carotenoids (Deruere et al, 1994). Other than the structural proteins fibrillins (described below), little is known about the protein composition of plastoglobules.…”
mentioning
confidence: 99%